2016
DOI: 10.2139/ssrn.2786877
|View full text |Cite
|
Sign up to set email alerts
|

Saving and Bequest in China: An Analysis of Intergenerational Exchange

Abstract: Particularly high saving rates among the elderly in both rural and urban China call for an investigation of the involved bequest motive. Utilizing unique survey data from a diverse group of Chinese households, we document that the magnitude of the bequest from parent to child is synchronized with the level of personal assistance from child to parent. Moreover, both bequest and assistance are increasing in the parent's income and decreasing in the child's income. Comparing with the prediction from a stylized ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, Alessie et al (2011) suggested that the higher financial literacy level reduces planning costs and decreases the barriers to the information required for saving and investing. The finding of Lusardi (2019) reveals that early-life education is a strong predictor of late-life financial knowledge and also suggests that enrollment rate at the school is a significant instrument in the first stage of financial education (Mancebon et al, 2019;Almas et al, 2020). Similarly, Beckmann (2013) argues that financial literacy is positively and significantly related to saving and investment.…”
Section: Logistic Regression Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, Alessie et al (2011) suggested that the higher financial literacy level reduces planning costs and decreases the barriers to the information required for saving and investing. The finding of Lusardi (2019) reveals that early-life education is a strong predictor of late-life financial knowledge and also suggests that enrollment rate at the school is a significant instrument in the first stage of financial education (Mancebon et al, 2019;Almas et al, 2020). Similarly, Beckmann (2013) argues that financial literacy is positively and significantly related to saving and investment.…”
Section: Logistic Regression Resultsmentioning
confidence: 97%
“…They concluded that the income category is the most important factor in being risk-tolerant (Sangeeta and Kanika, 2014;Trautman and Van de Kulien, 2018). Almas et al (2020) researched the Chinese context. Their results provided evidence that high saving rates among the young can be explained by credit constraints.…”
Section: The Mediating Effect Of Risk Aversion Levelmentioning
confidence: 99%
See 2 more Smart Citations